Motivation and satisfaction in online learning during COVID-19 pandemic: A systematic review - Nurfina Aznam; Jumadi Jumadi; Yusman Wiyatmo; Heru Nurcahyo; Riki Perdana (Institute of Advanced Engineering and Science, 2022)
The study summarized current studies on student motivation and satisfaction and identify research gaps for proposing studies for the next study. A total of 50 academic research papers on satisfaction and motivation during COVID-19 pandemic learning were published during pandemic era December 2019 to December 2020. There were 45,935 participants on the study with 357 elementary students, 478 middle-high students, 42,151 college students and 2,949 teachers. An important result of this study is a significant change in motivation and satisfaction. From the review, this paper updates a new database, with a wide range of student satisfaction and motivation through online learning during the COVID-19 pandemic, especially to improve student satisfaction and motivation for a successful learning process. Suggests that it can be considered an effective learning method. This study is beneficial for education experts, lecturers, teachers, trainers, and technologists who are interested in assessment, learning, guidance, design, and online-based learning environments during a pandemic or after a pandemic to increase motivation and satisfaction in learning.